Electrospun Nanofibers Derived from Food and Plant Waste in Wound Healing: A Review - Şenen, Büşra; Çiftçi, Fatih; Özerol, Esma Ahlatçıoğlu (Elsevier, 2026)
This study explores the integration of food waste valorization with electrospinning technology to develop advanced wound healing scaffolds. Chronic wound recovery is often hindered by oxidative stress and bacterial infections; however, electrospun nanofibers provide an ideal solution due to their high porosity and mimicry of the natural extracellular matrix. By repurposing a portion of the 1.3 billion tons of global annual food waste, this research utilizes sustainable biopolymers and bioactive compounds including polyphenols, flavonoids, and carotenoids for their potent antioxidant and antimicrobial properties. We analyze the incorporation of extracts from fruit peels (orange, mango, pomegranate), seeds, and industrial by-products into polymeric matrices like PCL, PVA, and cellulose. The resulting scaffolds significantly enhance cell proliferation and angiogenesis while advancing circular economy principles in biomedical engineering. Ultimately, transforming agricultural waste into multifunctional nanofibers offers a sustainable, clinically effective strategy for next-generation wound care management.
Keywords: Food and Plant Waste; Bioactive Compounds; Circular Economy; Electrospinning; Nanofibers; Sustainable Biomaterials; Wound Healing